The study of factor that influence guest selection in high-tariff a (5 star) hotel in Langkawi: “the case of the Ritz-Carlton Langkawi” / Ahmad Farid Syahmi Ros’haimi &Muhammad Sufieyan Abdul Fatah - Ros’haimi, Ahmad Farid Syahmi; Abdul Fatah, Muhammad Sufieyan (2018)
In today’s competitive environment, it is imperative that many guests are able to stay at any 5 star hotels. There are many factors to be considered when choosing to stay in a luxury hotel. The question of which factors are most important neither lease important is in the hand of the guest to be choose. Therefore, this study will investigate which of the factors that influence guest selection are important in a 5 stars hotel. The study was conducted in The Ritz-Carlton, Langkawi. This study used quantitative research and simple questionnaire was used as the instrument to measure which factors are most and lease important in the finding. A total of 50 respondents participated in this study with data collection in one month. The respondents had completed a questionnaire regarding factor that influencing them selection at this hotel. The finding was analysed by using Statistical Program for the Social Science software (SPSS). The result presented descriptive analyses based on the factor that influences guest selection at this 5 star hotel.